Penerapan Media Pembelajaran Berbasis Platform Quizalize dalam Meningkatkan Motivasi Belajar Peserta Didik - Nudia Fajarristianti; Aida Imtihana; Achmad Fadil (PAI RAFAH, 2025)
The low learning motivation of students in Islamic Religious Education (PAI) subjects has become a significant obstacle in achieving educational goals. This issue is reflected in the lack of enthusiasm, low participation, and teacher-centered learning activities that make students passive and easily bored. To overcome these problems, it is important to apply innovative and interactive digital learning media that can increase students’ engagement and motivation. One such medium is Quizalize, a digital learning platform designed to create a fun, competitive, and student-centered learning atmosphere. This study aims to determine the level of students’ learning motivation before and after the implementation of Quizalize in PAI subjects at SMP Tri Dharma Palembang. The research employed a quantitative approach with a one-group pretest–posttest design. The sample consisted of 26 students from class VIII A, selected using the purposive sampling technique. Data were collected through questionnaires, observations, and documentation, then analyzed using validity and reliability tests, the Shapiro–Wilk normality test, and the Paired Sample t-Test for hypothesis testing. The results show that students’ learning motivation increased from 57% to 74% after using Quizalize, indicating a 17% improvement. This finding demonstrates that the use of Quizalize-based digital learning media is effective in enhancing students’ learning motivation in PAI subjects. Therefore, the integration of interactive platforms like Quizalize in the learning process is recommended to make Islamic Religious Education more engaging, dynamic, and aligned with the needs of 21st-century learners.